Relationship between Emotional Intelligence and Students Attitude towards Co-Curricular Uniform Bodies in Malaysia - Yusof, Najeemah Mohd (EDUCARE, 2012)
ABSTRACT: The purpose of this study is to identify the relationship between emotional intelligence and students attitude towards co-curricular uniform bodies among secondary school children. The research is to determine the level of emotional intelligence, the difference between emotional intelligence based on gender and ethnicity, and relationship with studentsâ attitude towards uniform bodies. Sample for the study were 120 form four secondary school children from Penang, Malaysia. Emotional intelligence is measured using the Bar-On EQ-1:YV. The data were analyzed using the SPSS package version 16. The independent t-test was used to analyze whether there is any significant difference in the mean score of emotional intelligence based on gender. The one way ANOVA was used to analyze any significant difference in the mean score of emotional intelligence based on ethnicity. Pearson correlation was used to show the relationship between emotional intelligence and studentsâ attitude towards uniform bodies. The results show a significant difference and relationship which will be elaborated in this paper. The implication of this research is that the emotional intelligence should be emphasized in and outside the classroom as it is significant in improving studentsâ attitude and academic achievement.KEY WORDS: Emotional intelligence, students attitude, co-curricular activities, secondary school children in Malaysia, and human life.About the Author: Dr. Najeemah Mohd Yusof is a Senior Lecturer at the School of Educational Studies USM (Science University of Malaysia), 11800 Minden, Pulau Pinang, Malaysia. She can be contacted at: najineen@usm.myHow to cite this article? Yusof, Najeemah Mohd. (2012). âRelationship between Emotional Intelligence and Students Attitude towards Co-Curricular Uniform Bodies in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.5(1) August, pp.95-106. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2012); Revised (July 30, 2012); and Published (August 17, 2012).